Professionalism Apparatus Law Enforcement as a Factor Determinant of Legal Legitimacy in Society - Tusi Wirahayu Pertiwi; Muhamad Latif; Rudy Indrawan (Universitas Islam Darul Ulum, 2025)
The professionalism of law enforcement officers is a crucial factor in achieving just, effective, and legitimate law enforcement in society. In practice, however, law enforcement often reveals a gap between legal norms and social reality, frequently caused by low levels of professionalism among officers. This condition shows that the effectiveness of law enforcement depends not only on the clarity of legal norms but also on the quality of those who implement them. This study aims to analyze the professionalism of law enforcement from a socio-legal perspective and examine its implications for the legitimacy of law enforcement institutions. The research employs a socio-legal method that integrates normative legal analysis with an examination of the social dimensions of law enforcement practices. The findings indicate that professionalism extends beyond technical competence and procedural compliance, encompassing integrity, ethical conduct, independence, and sensitivity to social contexts. Weak professionalism contributes to selective law enforcement, discriminatory practices, and declining public trust in legal institutions. From a socio legal perspective, legal legitimacy is not solely derived from formal authority but is also constructed through public acceptance of how the law is applied. Law enforcement perceived as unfair, inconsistent, or lacking transparency undermines institutional credibility and weakens legal compliance. Therefore, strengthening the professionalism of law enforcement officers is essential not only to improve the quality of law enforcement but also to bridge the gap between law in the books and law in action, ensuring the sustainability of institutional legitimacy.